Endoscopic Features and Clinical Characteristics of Ulcerations With Isolated Involvement of the Small Bowel - Wu, Feng-fei; Xie, Qian; Huang, Xiao-shan; Wang, Wei-dong; Liao, Yan; Shi, Jie; Sun, Shi-bo; Bai, Lan; Xie, Fang (Turkish Journal of Gastroenterology, 2021)
Background: Double-balloon enteroscopy (DBE) enables the detection of ulcerations in the small bowel. However, determining an etiologicaldiagnosis remains challenging. This study was conducted to investigate the clinical and endoscopic features of ulcerations withisolated involvement of the small bowel (UIISB) to improve diagnostic ability.Methods: Patients (n = 565) who underwent DBE and presented with ulcerations in the small bowel at Nanfang Hospital from January2005 to January 2018 were eligible. Medical records were retrospectively examined. Predictors to determine ulceration etiology wereidentified by logistic regression analysis.Results: After excluding patients with extra-ulcerations in other sites (n = 306) and those without follow-up records (n = 50), 209 patientswith UIISB were enrolled. Among them, 59.3% of the ulcers were in the ileum, 26.8% in the jejunum, and 13.4% in the jejunoileum.Initial symptoms included abdominal pain (54.1%) and obscure gastrointestinal bleeding (30.0%). The multiplicity of ulceration wascategorized as a single (22.0%) or multiple (78.0%). Cases were diagnosed with Crohn’s disease (50.7%), chronic nonspecific inflammation(21.5%), diverticulum (9.1%), lymphoma (6.2%), gastrointestinal stromal tumor (4.3%), intestinal tuberculosis (1.9%), adenocarcinoma(1.4%), infective enteritis (1.4%), hemangioma (1.0%), cryptogenic multifocal ulcerous stenosing enteritis (1.0%), anastomoticulcer (0.5%), intestinal duplication (0.5%), or neuroendocrine tumor (0.5%). Etiology identification indicated the if patients were aged40 years or more, or had overt bleeding, single ulceration, and ulcer at jejunum, it as more prone to be neoplastic (P < .05).Conclusion: When we manage patients with UIISB, Crohn’s disease should be first under consideration. Age≥40, overt bleeding, singleulceration, and ulcer at jejunum were reasonable indications for etiology of neoplasm or non-neoplasm.